Comunidade quilombola Tanque do Padre Pinhal, Poconé-MT : educação, identidade, memória e territorialidade - Costa, Benedita Rosa da (2023)
This thesis was written as a result of doctoral research in Education, carried out in the quilombo remnant community of Tanque do Padre Pinhal, located in the rural area of the municipality of Poconé-MT. Concerned about the problem: does the quilombola cultural identity of students from the Tanque do Padre Pinhal quilombo community continue to be strengthened in the schooling process in basic education? The researcher's object of research is the curriculum of the school where students from the Tanque do Padre Pinhal quilombo remnant community carry out their schooling. The researcher used documentary analysis and studies on quilombo, based on Gomes (2006), Arruti (2008), Barreto and Prioste (2012), Costa (2021), Moura (1988), Carneiro (2001) and Munanga (2001). The work is structured as follows: Chapter I presents the author's memoir, highlighting her life trajectory and quilombola identity, pointing out quilombola identity as a collective construction and her academic, professional and political trajectory. Chapter II discusses Quilombola identity and school education according to the National Curriculum Guidelines for Quilombola School Education in Basic Education. These include Historical Narratives about Quilombo, Memory as the Storage of Lived Histories, Quilombola Territory as the Cradle of the Remnant Community, Education as a Formative Process in Different Realities, Quilombola Education and School Education. Chapter III covers the methodological paths, describing the choice of methodology, the research approach, the path the researcher took beforehand, contact with the community, the choice of participants, the days of the conversation, the subjectivities of the residents. Chapter IV deals with the Quilombola Cultural Identity of Students from the Tanque do Padre Pinhal Remnant Quilombo Community: Resistance and Vulnerability in the Educational Context. The Final Considerations present the theoretical discussions that were considered and the results of the analysis that the research pointed to in order to prepare the thesis. It is hoped that the results of the research will contribute to the debate on school education and the formation of Quilombola cultural identity in basic education; subsidize studies, research, curricular composition and pedagogical practices, as well as demands for public policies and better conditions for their translation into everyday school life. RESUMEN : Esta tesis fue escrita como consecuencia de una investigación de doctorado en Educación, realizada en la comunidad quilombola remanente de Tanque do Padre Pinhal, localizada en el área rural del municipio de Poconé-MT. Preocupada por el problema: ¿la identidad cultural quilombola de los alumnos de la comunidad quilombola Tanque do Padre Pinhal continúa siendo fortalecida en el proceso de escolarización en la enseñanza básica? El objeto de investigación de la investigadora es el currículo de la escuela donde los alumnos de la comunidad remanente quilombola Tanque do Padre Pinhal realizan su escolaridad. La investigadora utilizó análisis documentales y estudios sobre el quilombo, basados en Gomes (2006), Arruti (2008), Barreto y Prioste (2012), Costa (2021), Moura (1988), Carneiro (2001) y Munanga (2001). La tesis está estructurada de la siguiente manera: el capítulo I presenta las memorias de la autora, destacando su trayectoria de vida y su identidad quilombola, señalando la identidad quilombola como construcción colectiva y su trayectoria académica, profesional y política. El capítulo II aborda la identidad quilombola y la educación escolar según las Directrices Curriculares Nacionales para la Educación Escolar Quilombola en la Enseñanza Básica. Se abordan las narrativas históricas sobre el quilombo, la memoria como almacenamiento de historias vividas, el territorio quilombola como cuna de la comunidad remanente, la educación como proceso formativo en diferentes realidades, la educación quilombola y la educación escolar. El capítulo III aborda los caminos metodológicos, describiendo la elección de la metodología, el abordaje de la investigación, el camino previo recorrido por el investigador, el contacto con la comunidad, la elección de los participantes, los días de la conversación, las subjetividades de los residentes. El Capítulo IV trata de la Identidad Cultural Quilombola de los Alumnos de la Comunidad Quilombo Remanente del Tanque do Padre Pinhal: Resistencia y Vulnerabilidad en el Contexto Educativo. Las Consideraciones Finales presentan las discusiones teóricas que fueron consideradas y los resultados de los análisis que la investigación reveló para la tesis. Se espera que los resultados de la investigación contribuyan al debate sobre la educación escolar y la formación de la identidad cultural quilombola en la enseñanza básica; subsidien estudios, investigaciones, composición curricular y prácticas pedagógicas, así como demandas de políticas públicas y mejores condiciones para su traducción en el cotidiano escolar.